The Dietary Intake of Children Aged 6 to 59 Months and their Hemoglobin Concentration, Central Highland Ethiopia, Community Based Baseline Data - Ferede, Abebe; Belachew, Tefera; Abera, Muluemebet (International Journal of Child Health and Nutrition, 2022)
Iron deficiency anemia (IDA) in young children has lacked attention and priority in developing countries where illiteracy is the greatest encumbrance in the community. This study aimed to assess the hemoglobin level (Hgb) and linear growth of children for baseline data for optional intervention. Methods: Community-based cross-sectional study was carried out among women and their paired children. A multistage sampling method was involved in selecting the study area and 1012 mothers/caregivers and their paired children. Interviewed, blood samples, and anthropometry data were collected and analyzed using IBM SPSS Statistics version 21. Statistical significance was declared at P<0.05 Results: All mothers with their paired children participated in the study. A high proportion (76.7%, n=776) of women aged 20 to 35 years and 505 (59.9%) of women had an awareness of IDA. The mean Hgb concentration of children was 128.23g/L (+ 17.3), and 184 (18.4 %) of the children had anemia, which was higher (24.1%) among age groups 6 -23 months. The highest proportion (42.1%, n = 426) of the children had stunted growth (Height for Age [HFA] Z score < -2 Standard Division [SD]) and a very high prevalence (24.6%, n = 251) of wasting (Weight for Height [WFH] Z score >-1SD) verified among children. The age of children is positively associated with Hgb level (β = 0.172, CI=0.01, 0.33). For a one-month increase in age, Hgb concentration increased by 0.170 mg/del. Conclusions: A very high growth defect and moderate IDA were observed among study subjects. Attentive intervention approaches are important in self-monitoring and a routine modification of used household foods in complementary feed with efficient iron nutrients to reduce growth defects.